Thin film tandem nanoplasmonic photoconductive antenna for high performance terahertz detection. (August 2018) - Ghorbani, Saman; Bashirpour, Mohammad; Poursafar, Jafar; Kolahdouz, Mohammadreza; Neshat, Mohammad; Valinejad, Amirali
Abstract: Photoconductive antennas (PCA) have attracted lots of attention for terahertz application, due to their room temperature operation and compact design. On the other hand, their main problem is acquiring low output power. Lately, plasmonic structures of different geometries have been proposed to overcome the mentioned issue. Here, we have proposed and simulated a PCA on a silicon-on-sapphire substrate and a layout of a plasmonic nanostructure in which the effect of geometrical parameters of the nanostructure on PCA's output was investigated and optimized. According to the results for one layer plasmonic nanostructure, two different geometries showed more than 700% improvement in the device photocurrent which are related to different types of surface plasmons. By combining these layouts and benefiting from both simultaneously, a final proposed nanostructure was constructed. After optimizing the new structure's parameters, a significant increase of 15400% in photocurrent enhancement was achieved by comparing to the conventional THz PCAs on similar substrate. Highlights: A new double layer nanoplasmonic structure is proposed in the gap of a PCA. Significant enhancement in optical absorption by strong coupling of LSPs and SPPs. Complete investigation of one layer and double layer nanostructures' parameters. Analytical confirmation of simulation results. 11400% improvement in photocurrent of new PCA compared with the conventional PCA.